The CORE Learning Model of Junior High School Students for Improving the Mathematical Reasoning Ability - Khairini Atiyah; Nanang Priatna (Universitas Swadaya Gunung Djati, 2023)
Abstract. Mathematical reasoning is a skill that must be owned by students. The lack of students' reasoning ability is caused by the teacher's lack of ideas in applying the learning model. The CORE is one of the appropriate learning models to be applied in class This study aims to determine the effect of the CORE learning model on the mathematical reasoning ability of junior high school students, to describe the improvement in students' mathematical reasoning ability after the implementation of the CORE and to determine the advantages of the CORE from the analysis of several literatures library. The research approach used is qualitative literature study. The data collection method used is documentation, which is like tracing written sources that contain the same topics and themes as this study, namely the application of the CORE to improve the mathematical reasoning ability of junior high school students. The results showed that the student's responses to the CORE learning model were positive. The results of this study are that the CORE influence students' mathematical reasoning ability in mathematics learning and the CORE learning model can improve junior high school students' mathematical reasoning ability.Keywords: CORE Learning Model, Mathematics, Mathematical Reasoning.